Nutritional Potential of Ziziphus lotus (L.) Lam. Almonds as Compared to Some Oilseeds from Morocco: Evidence from Proximate Composition, Mineral Profiling, and Oil Physicochemical Traits - Hasna Ait Bouzid; Laila Bijla; Mohamed Ibourki; Abderrahim Asbbane; El Hassan Sakar; Jamal Koubachi; Said Gharby (Journal of Food Quality)
Nowadays, there is a great interest in the search for new sources of vegetable oils, natural bioactive compounds, and essential nutrients for human health. Oleaginous fruits and seeds are a good source of nutrients such as oil, carbohydrates, fatty acids, sterols, tocopherols, fibers, vitamins, minerals, and proteins for the human diet. The main objective of this study was to compare the nutritional composition of Ziziphus lotus almonds (ZLA) with some well-known seeds (argan kernel, nigella seed, cactus seed, and sesame seed) and to classify them by the mean of principle component analysis (PCA). The samples’ proximate composition, mineral profiling, and some physicochemical parameters of extracted oil were evaluated. Our results revealed that ZLA composition was as follows: oil yield (26.99 ± 1.52 g/100 g), proteins (30.79 ± 0.07 g/100 g), ash (6.5 ± 0.06 g/100 g), and moisture (3.62 ± 0.10 g/100 g). The mineral profile of ZLA consists mainly of P, K, Mg, and Ca. The main fatty acids in ZLA oil were oleic acid (60.73 ± 0.10 g/100 g), linoleic acid (18.75 ± 0.10 g/100 g), and palmitic acid (9.86 ± 0.10 g/100 g). β-Sitosterol (67.92 ± 0.46 g/100 g) was the major sterol in ZLA, followed by stigmasterol (15.34 ± 0.35%) and campesterol (8.75 ± 0.12%). Total tocopherols were present at 523 ± 9.23 mg/kg in the oil. PCA analysis demonstrated that the ZLA composition was found to be close to that of sesame seeds. In conclusion, ZLA could be considered an alternative source of vegetable oils and protein as well as other various applications.